2016
DOI: 10.1016/j.radcr.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Glenoid hypoplasia

Abstract: Glenoid hypoplasia, also known as glenoid dysplasia and dysplasia of the scapular neck, is a failure of ossification of the posteroinferior two-thirds of the glenoid. Once thought to be a rare condition, more recent studies have shown that the incidence of glenoid hypoplasia ranges from 18% to 35%. This case report and literature review highlights the typical clinical presentation, the radiologic findings, and the management options for patients with glenoid hypoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Glenoid dys- or hypoplasia may occur as a primary isolated condition or in association with various syndromes [ 1 ]. Once thought to be a rare condition, more recent studies have shown that the incidence of glenoid hypoplasia ranges from 18 to 35% [ 2 ]. The glenoid morphology was originally classified by Walch in 1999 and has recently been modified [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glenoid dys- or hypoplasia may occur as a primary isolated condition or in association with various syndromes [ 1 ]. Once thought to be a rare condition, more recent studies have shown that the incidence of glenoid hypoplasia ranges from 18 to 35% [ 2 ]. The glenoid morphology was originally classified by Walch in 1999 and has recently been modified [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%